Suppurative mediastinitis due to esophageal perforation due to impacted foreign body - Praderi, Luis; Vega, Dardo; ´Berois, Néstor; Pravia, Juan A; López, Juan (Cirugía del Uruguay, 1972)
The paper deals with a rare case of esophageal thoracic perforation dueto migration of a fishbone. Contrasted radiology established its diagnosis and topography. It was treated successfully by a left thoracomediastinomy, coupled with frenotomy so as to discard a second abdominal perforation.